Studi Komposisi Pigmen Makro Alga (Gelidium corneum) yang Berasal Dari Pantai Yakoba Kota Jayapura - Tien Nova B. Yenusi; Jotje A. Ingratubun (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Macroalgae or also known as seaweed is a low-level plant that does not have true roots, stems and leaves. The function of the roots, stems and leaves is replaced by the thallus. The purpose of this study was to study the composition of macroalgae pigments (Gelidium corneum) originating from Yakoba Beach, Jayapura City. The method used in this research is an experimental method with pigment analysis using Thin Chromatography and Visible UV Spectrophotometry. The TLC plate test shows the results of identification of the crude extract of the Gelidium corneum pigment. The first three spots are green with an Rf value of 0.24 identified as chlorophyll compounds, the second spot is blue green which is identified as chlorophyll a compound with an Rf value of 0.26 and the third spot was green and yellow identified as chlorophyll b compound with an Rf value of 0.33. The absorbance pattern or wavelength (nm) from the results of the identification of this pigment shows that there are 3 highest peaks identified as chlorophyll pigments where the absorption pattern is at a wavelength of 350-700 nm (Habone, 1987 in Doli et al, 2020).